2022
DOI: 10.48550/arxiv.2203.13297
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The catastrophic fate of Schwarzschild black holes in a thermal bath

Abstract: Using the Schwazchild metric as a rudimentary toy-model, we pedagogically revisit the curious prediction that the mass of a classical black hole in a constant temperature thermal bath diverges in a finite amount of time. We study in details how this instability behaves if the temperature of the bath is allowed to vary with time and conclude that whatever the background behavior (but for a zero-measure subspace of the initial conditions), the black hole mass either diverges or vanishes in a finite time if the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The thermal properties of black holes possess a subtle and an intriguing feature, which is often overlooked, but was recently brought to a central stage by Barrau, Martineau and Renevey in Ref. [1]. As it is well known, the energy density of thermal radiation is proportional to the fourth power of its absolute temperature T .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The thermal properties of black holes possess a subtle and an intriguing feature, which is often overlooked, but was recently brought to a central stage by Barrau, Martineau and Renevey in Ref. [1]. As it is well known, the energy density of thermal radiation is proportional to the fourth power of its absolute temperature T .…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. [1] the effective radius of the Schwarzschild black hole was taken to be, in the natural units, 3 √ 3M , and the authors found that Eq. (1.1) takes the form:…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations